2016
DOI: 10.1038/ja.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of acyl carrier proteins by ketoreductases in assembly line polyketide synthases

Abstract: Ketoreductases (KRs) are the most widespread tailoring domains found in individual modules of assembly line polyketide synthases (PKSs), and are responsible for controlling the configurations of both the α-methyl and β-hydroxyl stereogenic centers in the growing polyketide chain. Because they recognize substrates that are covalently bound to acyl carrier proteins (ACPs) within the same PKS module, we sought to quantify the extent to which protein-protein recognition contributes to the turnover of these oxidore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
0
20
0
2
Order By: Relevance
“…A., T. R., and B. L. designed the study. M. K. purified the proteins, constructed TE-knockout mutants, and carried out the NADPH consumption, LC-MS analysis, and 14 C radiolabeling experiments. J.…”
Section: Radioisotopic Sds-page Labeling Assay-[1-mentioning
confidence: 99%
See 2 more Smart Citations
“…A., T. R., and B. L. designed the study. M. K. purified the proteins, constructed TE-knockout mutants, and carried out the NADPH consumption, LC-MS analysis, and 14 C radiolabeling experiments. J.…”
Section: Radioisotopic Sds-page Labeling Assay-[1-mentioning
confidence: 99%
“…Following destaining with water for 5 min, the gel was mounted on a filter paper and dried in vacuo for 2 h using a Bio-Rad 543 gel dryer. The dried gel was imaged for 1 h lane by lane to quantify 14 C on individual protein bands using a Rita Star TLC Analyzer (Raytest). Peaks were integrated to quantify the radiolabel bound to each protein.…”
Section: Radioisotopic Sds-page Labeling Assay-[1-mentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of additionally analyzing the contribution of ACP:KS recognition and substrate:KS interaction on the turnover of KS mutants, we generated alternative M1 donor modules that would allow us to probe the remaining ACP-substrate combinations ( Figure 4&5). Based on the observations that KR domains can efficiently turn over with a variety of chimeric ACPs, 39 and that chain elongation at a chimeric ACP:KS interface in a fusion protein is not rate-limiting, 22 we generated 6 alternative M1 donors by permutating KR1 and ACP1. The exchange of ACP1 with ACP2 and ACP5, the native upstream ACPs of M3/M6, generated donor modules carrying NDK on the respective ACP ( Figure 4A, donor 2 & Figure 5A, donor 5).…”
Section: Using Different Donor Acp-substrate Combinations To Analyze mentioning
confidence: 99%
“…These advances in re-engineering the stereochemical outcomes of the KR domain has been complemented by investigations into its ACP specificity. The interaction landscape of four reducing KRs from DEBS and five ACPs from DEBS was assessed in a simple in vitro assay [ 87 ]. The outcomes showed that KRs often exhibit a modest preference for their cognate ACPs by a factor of 10- to 50-fold, although this rule was violated by KR6, which preferred ACP5 instead.…”
Section: Ketoreductase: Modular Context and Catalysismentioning
confidence: 99%